Comparison Between Hallux Rigidus Parameters Assessed by Conventional Radiographs and Weight- Bearing CT. Issue 4 (November 2022) - Carvalho, Kepler; Pinto, Martim d.; Vivtcharenko, Victoria; Den Hartog, Taylor; Ehret, Amanda; Dibbern, Kevin N.; Lee, John; Femino, John E.; Lalevée, Matthieu; Netto, Cesar de Cesar
Category: Midfoot/Forefoot; Other Introduction/Purpose: The etiology of hallux rigidus (HR) is not well understood and its association with first-ray hypermobility, hallux valgus and metatarsus primus elevatus (MPE) has not been clearly proven. Recent studies have supported MPE in HR by measuring on weightbearing radiographs (WBR), but there are limitations of WBR due to variation in X-ray projection and superimposed metatarsals. WBCT represent a reliable tool for radiographic analysis of the first ray and can be important for the study pathologies such as HR, which involve several anatomical points to be evaluated for a correct clinical- radiographic diagnosis Our objective was to evaluate radiographic parameters associated with Hallux Rigidus via WBR and WBCT for convergent validity and to evaluate the use of the classification system used in conventional radiography with WBCT. Methods: This is a single-center, retrospective study from prospectively collected data. 20 symptomatic hallux rigidus patient with weightbearing radiograph and WBCT were enrolled from October 2014 to December 2020. Measured parameters included hallux valgus angle (HVA), intermetatarsal angle (IMA), 1st TMT joint version, First and second metatarsal lengths, 2nd cuneiform- 2nd metatarsal angle, Talus-1st Metatarsal angle, First and second metatarsal declination angles, and MPE. MPE was measured as the direct distance between 1st and 2nd metatarsals (modified Horton index). All patients were graded according to the radiographic criteria of Coughlin and Shurnas classification on radiographs and WBCT, separately. Paired T-test was performed to compare radiographic measurements with WBCT. Results: Mean age was 55.9. HVA (15.73° in X-ray vs 14.04° in WBCT), AP first TMT version (16.25° vs 16.47°), 2nd cuneiform- 2nd metatarsal angle (24.54° vs 26.60°), Talus-1st Metatarsal Angle (-7.67° vs -7.89°) were not different between radiograph and WBCT. MPE was measured higher in WBCT by 0.86 mm compared to radiograph. First metatarsal declination angle was lower in WBCT by 2.9° indicating increased MPE. When graded with radiographic findings, 5 (25%) patients were grade 1, 5 (25%) patients were grade 2 and 10 (50%) grade 3, when graded with WBCT, 1 (5%) patient had grade 1, 3 (15%) patients were grade 2 and 16 (80%) grade 3. When graded radiologically, subchondral cyst in proximal phalanx and metatarsal head were better delineated resulting in higher radiographic grade with WBCT. Dorsal subluxation/translation of first metatarsal at first TMT joint was observed 3 (15%) in radiograph and 9 (45%) in WBCT. Conclusion: Hallux Valgus Angle, AP first TMT version, 2nd cuneiform-2nd metatarsal angle, Talus-1st Metatarsal Angel demonstrated consistent measurements in radiograph and WBCT. MPE was measured higher in WBCT when measured with direct distance (0.86 mm) between the first and second metatarsals using modified Horton index and first metatarsal declination angle (2.9°). When graded with WBCT, the subchondral cyst in the proximal phalanx and metatarsal head were better delineated leading to higher grade in WBCT which infer WBCT grading system for HR can aid in early detection of advanced HR with high radiographic grades and potentially guide treatment accordingly.